Faktor-Faktor yang Mempengaruhi Keberhasilan Implementasi Activity-Based Costing (ABC) di Indonesia - Tumiar Deliana Gultom; Kholifah Kholifah; Ratih Kusumastuti (Jurnal Mutiara Ilmu Akuntansi, 2023)
Even though Activity Based Costing (ABC) has been implemented by large companies in Indonesia, there are still obstacles that limit its implementation, such as high implementation costs and the long time required. The aim of this research is to find out what factors influence the success of the implementation of Activity Based Costing (ABC) in Indonesia. The type of research is a descriptive method with a qualitative approach. The data used in this research was obtained from the results of a literature review of these articles. The research results show that management understanding and commitment are the main factors influencing the success of implementation. The constraints of high implementation costs and the long time required are special concerns in implementing ABC in Indonesia. Technology support and staff skills determine the smoothness of the implementation process. Implementing ABC requires activity mapping, identification of cost drivers, and appropriate cost allocation to optimize resources and improve company performance.